Crowding-In Capital Attracts Institutional Investors to Emerging Market Infrastructure through Co-Lending Platform - Lauridsen, Morten Lykke; Chastenay, Carl; Kurdyla, Michael (International Finance Corporation, Washington, DC, 2018)
Financing infrastructure in emerging markets is a critical global challenge for sustainable development. Through a new International Finance Corporation (IFC) program, private institutional investors can directly participate in the evolving infrastructure asset class in emerging markets. The program, IFC’s managed co-lending portfolio program for infrastructure, creates a structure that overcomes several hurdles that have inhibited the flow of private capital to emerging market infrastructure projects. It provides an innovative model to mobilize financing for development that combines financing from insurance companies, project origination and credit enhancement from IFC, and support from public sector donors.